THE INFLUENCE OF AI LITERACY, ETHICAL AWARENESS, AND TRUST IN DIGITAL AUDIT TECHNOLOGY ON ACCOUNTING STUDENTS' READINESS TO FACE THE ACCOUNTING PROFESSION IN THE ERA OF ARTIFICIAL INTELLIGENCE (A CASE STUDY ON ACCOUNTING STUDENTS IN LAMONGAN REGENCY) - Silfi Yaturrahmah; Novi Darmayanti; Martha Laila Arisandra (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2026)
This study aims to determine the influence of AI literacy, ethical awareness, and trust in digital audit technology on the readiness of accounting students to face the profession in the AI era. The research uses a quantitative approach with a causal associative design. Data were collected through an online questionnaire from 100 accounting students in Lamongan selected using purposive sampling. The data were analyzed using multiple linear regression with SPSS. The results show that AI literacy and trust in digital audit technology have a positive and significant effect on student readiness, while ethical awareness does not have a significant effect. Simultaneously, all three variables contribute to student readiness. These findings indicate the importance of strengthening AI-based learning and building students’ confidence in digital audit tools. This study develops a model of accounting students’ readiness in the Artificial Intelligence era by simultaneously integrating AI literacy, ethical awareness, and trust in digital audit technology.